1983
DOI: 10.1111/j.1476-5381.1983.tb10509.x
|View full text |Cite
|
Sign up to set email alerts
|

Electrophysiological effects of imipramine in non‐treated and in imipramine‐pretreated rat atrial fibres

Abstract: The effect of imipramine (Imip) in concentrations between 10−7M and 5 × 10−5M has been studied on rat atrial transmembrane potentials. In another group of experiments the effect of Imip was studied in atrial fibres from rats pretreated for 24 days with twice daily intraperitoneal injections of Imip 7.5 mg/kg or saline. In non‐treated atria Imip depressed action potential amplitude and Vmax, reduced the resting membrane potential and shifted the membrane responsiveness and recovery time curves downward and to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0

Year Published

1985
1985
2004
2004

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 22 publications
3
11
0
Order By: Relevance
“…Thus, the addition of therapeutic concentrations of amoxapine to the perfusate produced similar changes in untreated and pretreated atria. These results are in contrast to those obtained with imipramine (Manzanares & Tamargo, 1982) and could explain why adverse cardiovascular effects are rarely observed during chronic treatment of depressed patients with amoxapine (Smith & Ayd, 1981;Jue et al, 1982). One possible reason for the differences between imipramine and amoxapine could be related to the pharmacokinetics of these compounds.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…Thus, the addition of therapeutic concentrations of amoxapine to the perfusate produced similar changes in untreated and pretreated atria. These results are in contrast to those obtained with imipramine (Manzanares & Tamargo, 1982) and could explain why adverse cardiovascular effects are rarely observed during chronic treatment of depressed patients with amoxapine (Smith & Ayd, 1981;Jue et al, 1982). One possible reason for the differences between imipramine and amoxapine could be related to the pharmacokinetics of these compounds.…”
Section: Discussionmentioning
confidence: 76%
“…Moreover, very recently Manzanares & Tamargo (1982) have demonstrated that the inhibition of the fast inward Na current induced by imipramine was potentiated in rats chronically treated with imipramine. Unfortunately, the electrophysiological effects of amoxapine have not been previously studied in isolated cardiac fibres.…”
Section: Introductionmentioning
confidence: 99%
“…The effects of imipramine on action potential duration (APD) show important species dependence. In bovine ventricular [ 75 ] and Purkinje fibers [ 65 ], guinea-pig papillary muscles [76][77] and isolated ventricular myocytes [ 70 ] imipramine shortened the APD, whereas in rabbit and rat atrial fibers [78][79] it lengthened the APD. The different effects of imipramine on APD can be explained by the important differences in the ionic currents responsible for the repolarization among animal species.…”
Section: Cellular Electrophysiological Effects Of Tcas-mentioning
confidence: 99%
“…TCAs are also known to have a local anaesthetictype action on peripheral excitable tissue (Ritchie & Greengard, 1961;Seeman et al, 1974;Schauf et al, 1975;Wang et al, 1981;Manzanares & Tamargo, 1983). This has led to the 'impulse blocking' hypothesis of antidepressant action (Randal, 1981), although it has generally been considered that concentrations of TCAs above the therapeutic range were necessary for neuronal block.…”
Section: Introductionmentioning
confidence: 99%